2011
DOI: 10.1007/s10833-011-9173-y
|View full text |Cite
|
Sign up to set email alerts
|

Why is school reform sustained even after a project? A case study of Bac Giang Province, Vietnam

Abstract: This paper reports on a case study of schools in Vietnam wherein teachers are engaged in school reform activities known as professional teacher meetings (PTMs), which is based on an approach called lesson study for learning community (LSLC). The PTMs under LSLC were introduced in 2006, but the teachers involved are still conducting the activities despite scarcity of resources, particularly technical ones. This study addresses the following research question: Why have teachers continued to organize PTMs after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 30 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…The principal retired in 2004, and since then, LSLC has been sustained as the school policy. This tendency of sustainability for a long period is also found in Vietnam (Saito et al, 2011). Further investigation needs to be conducted on the kind of leadership that is required to sustain LSLC for such a long period.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The principal retired in 2004, and since then, LSLC has been sustained as the school policy. This tendency of sustainability for a long period is also found in Vietnam (Saito et al, 2011). Further investigation needs to be conducted on the kind of leadership that is required to sustain LSLC for such a long period.…”
Section: Discussionmentioning
confidence: 82%
“…In this particular approach, from the beginning of the process the entire school is involved as a learning organization based on systems thinking (Senge, 2006). The research into the practices of LSLC in the international literature is, however, extremely limited except for a few studies of Vietnamese cases Saito et al, 2011).…”
Section: Issues In Previous Researchmentioning
confidence: 99%
“…With the adaptation of Japanese LS globally, researchers have explored the factors that impact the effectiveness of implementation of LS (Fernandez 2002;Lim et al 2011;Perry and Lewis 2009;Saito et al 2012). These factors are classified into two broad categories: macro-level conditions, which are related to education systems, and micro-level conditions, which are related to individual participants.…”
Section: Constraints and Challenges In Adaption Scaling-up And Sustmentioning
confidence: 99%
“…These factors include "establishing authentic professional communities able to address conflicting ideas and build teachers' knowledge; breaking down traditional hierarchical relationships within the system and walls that keep classroom practices private; focusing on student thinking; taking initiative to draw on external knowledge resources; and realizing that the shared research lesson (an unfamiliar form) can provide a solid basis for collaborative reflection about students' progress toward instructional goals" (p. 387). Saito et al (2012) reported that a variation of LS called a LS for Learning Community was implemented in a school reform project. They found that the LS can be successfully sustained in schools where the school leaders provide strong support, and teachers are convinced of its effectiveness.…”
Section: Macro Level Conditionsmentioning
confidence: 99%
“…Saito et al (2016) introduced the case of the deconstruction of bureaucratic teachers’ values and behaviours through discussions on lesson study where teachers tried to place perspectives of social justice and care-based learning at the centre of reflective discussion. They did this by disclosing lessons to all the participants of school, reflecting on the lessons the teachers had come to observe, listening to students and revoicing students’ difficulties and achievements (Saito, Khong, & Tsukui, 2011; Saito & Tsukui, 2008). Using videos that were easily available on smart phones enabled teachers in school to immediately reflect on their practice in classrooms and on whether their lessons realized the alternative underlying values the way they wanted (Saito & Khong, under review).…”
Section: Introductionmentioning
confidence: 99%